Prevalence and factors associated with laboratory-confirmed cases of select enteric infections in three Ethiopian communities, 2018-2022 - LaPolt, D.; Azmeraye, B.M.; Kuang, Z.; Degefaw, D.; Teshale, A.M.; Alonso, Silvia; Dessie, Y.; Lopez, M.; Kalayu, A.A.; Andargie, G.; Kowalcyk, B. (2025)
Enteric diseases are major contributors to morbidity and mortality worldwide; however, in Ethiopia, information on the prevalence of enteric infections and associated trends is limited. Understanding the epidemiology of enteric infections is necessary for determining disease burden and allocating resources. The objective of this study was to estimate the prevalence of laboratory-confirmed infections associated with select parasitic and bacterial pathogens in three Ethiopian hospitals, assess trends, and identify associated factors. Laboratory and patient metadata for stool samples tested at clinical laboratories in Addis Ababa, Gondar, and Harar in Ethiopia from 2018 through 2022 were collected and digitized. Descriptive statistics were used to summarize laboratory results and assess trends in sample submission and infection. Prevalence of laboratory-confirmed infection and 95% confidence intervals were estimated by pathogen using binomial proportion testing and logistic regression. Univariate and multivariable logistic regression were used to identify associated factors. A total of 48,643 samples were included in the analysis. Prevalence estimates for parasitic infection were 5.23% [95%CI:4.87%,5.62%], 17.48% [95%CI:17.04%,17.93%], and 15.69% [95%CI:14.57%,16.85%] in Addis Ababa, Gondar, and Harar, respectively. Prevalence estimates for bacterial infection were 0.25% [95%CI:0.07%,0.65%] and 7.59% [95%CI:5.97%,9.50%] in Addis Ababa and Gondar, respectively; stool samples were not tested for bacterial pathogens in Harar. Stool sample submission and enteric infection detection varied by year at each site. Age, season, and year of submission were identified as factors associated with the detection of enteric pathogens in stool samples. Prevalence estimates differed across study sites and testing was not conducted for many enteric pathogens associated with diarrhea. Additional research to understand the scope of enteric infection is necessary for resource allocation toward robust diagnostic procedures and increased laboratory capacity for stool testing. Efforts to mitigate enteric infection should utilize seasonal and geographic infection trends to anticipate areas in need of additional resources.